2018
DOI: 10.21037/jtd.2018.04.41
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical treatment in patients with pulmonary embolism and thrombus-in-transit

Abstract: Background: Floating right heart thrombi (RHT) are in transit from the legs to the pulmonary arteries and thus are a severe form of venous thromboembolism (VTE), with a high early mortality rate without treatment. There is a lack of evidence-based recommendations for its management. The objective of this study is to describe our experience in the surgical management of thrombus-in-transit and pulmonary embolism (PE) in a tertiary hospital. Methods: We recruited four patients with thrombus-in-transit and PE tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Moreover, the timing of these procedures seems to have a critical role as most patients who survived surgical thrombectomy had the intervention planned and carried out in the first few hours of presentation. 12 , 51 54 Such factors, along with the plethora of evidence supporting the use of thrombolytic therapy in PE, its easy availability, and reduced needs for expertise (compared to surgical thrombectomy or percutaneous thrombectomy) may explain the more established role of thrombolytic therapy in various types of PE as compared to surgical thrombectomy and percutaneous thrombectomy. Interestingly, we found a half-dose (50 mg alteplase) used in a case series of five patients, with excellent outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the timing of these procedures seems to have a critical role as most patients who survived surgical thrombectomy had the intervention planned and carried out in the first few hours of presentation. 12 , 51 54 Such factors, along with the plethora of evidence supporting the use of thrombolytic therapy in PE, its easy availability, and reduced needs for expertise (compared to surgical thrombectomy or percutaneous thrombectomy) may explain the more established role of thrombolytic therapy in various types of PE as compared to surgical thrombectomy and percutaneous thrombectomy. Interestingly, we found a half-dose (50 mg alteplase) used in a case series of five patients, with excellent outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that over 90% of FFRHT can end up in PE. 12,21 Furthermore, despite the lack of previous studies documenting the correlation between the hemodynamic consequences and the size of the FFRHT, the latter seems another plausible explanation that warrants further evaluation. Finally, the lack of a clear consensus and guidelines specific to the management of FFRHT in association with PE could have contributed to the dismal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, Galeano-Valle et al 1 . reported the surgical management of thrombus-in-transit and pulmonary embolism (PE) in four patients treated with early surgical embolectomy and anticoagulation.…”
Section: Discussionmentioning
confidence: 85%
“…Due to the complexity of the patients and the lack of randomized studies, we continue debating the best therapy for our patients. Different therapeutic approaches for acute PE with concomitant TT have been reported such as anticoagulation with unfractionated heparin (UFH), systemic thrombolysis with recombinant tissue plasminogen activator (rTPA), surgical embolectomy with exploration of the right chambers, pulmonary arteries under full cardiopulmonary bypass, and endovascular thrombectomy 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation